Sea breeze at Monterey Bay: comparisons between Lidar measurements and two-dimensional numerical simulations - Darby, Lisa S., author (Colorado State University. Libraries, 2001)
The NOAA/ETL TEA CO2 Doppler lidar measured the life cycle of the land- and sea-breeze system along the California coast under various synoptic conditions during the Lan and Sea Breeze Experiment (LASBEX) in September, 1987. The lidar was stationed at Moss Landing, 1.5 km east of the shore of Monterey Bay, measuring winds on 12 days. On days with offshore synoptic flow , the transition to onshore flow (the sea breeze) was a distinct process easily detected by lidar. Fine-scale lidar measurements showed the reversal from offshore to onshore flow near the coast, and its gradual vertical and horizontal expansion. Lidar scans taken along an east/west cross-shore line, horizon-to-horizon, on days with ambient offshore flow, showed a dual structure to the sea breeze flow in its early formative stages. First, a shallow (<500 m) sea breeze formed which late became embedded in a weaker onshore flow that was -1 km deep. Eventually these two flows blended together to form a mature sea breeze at least 1 km deep. Regional Atmospheric Modeling System (RAMS) two-dimensional simulations successfully simulated this dual structure of the sea breeze flow when both the coastal mountain range just east of Monterey Bay and the Sierra Nevada range, peaking 300 km east of the shore, were included in the domain. Various sensitivity simulations were conducted to isolate the roles played by the land/water contrast, the coastal mountain range, and the Sierra Nevada range. Notable results include 1) the Sierra Nevada Range greatly affected the winds above 1500 mat the shore, even though the peak of the mountain range was 300 km east of the shore, 2) the winds at the shore, below 1500 m, were most affected by the land/sea contrast and the coastal mountain range, and 3) the presence of the coastal mountain range enhanced the depth of the sea breeze flow, but not necessarily the speed of it. A factor separation method was employed to further isolate the contributions of the terrain and land/water contrast to the vertical structure of the modeled u-component of the wind. When both mountains were included in the domain, the interaction of the slope flows generated by these mountains acted to strongly enhance onshore flow early in the morning, and then enhance a return flow layer during the day. In contrast, the interaction of flows generated by the land/water contrast and the sloping terrain had its strongest effect late in the afternoon and early evening, working to oppose the sea breeze flow. The triple interaction of the flows generated by the coastal mountain, inland mountain, and the land/water contrast enhanced the sea breeze flow from the surface to 500 m ASL throughout the day.
Spring 2001.
Also issued as author's thesis (M.S.) -- Colorado State University, 2001.
Keywords: Ocean-atmosphere interaction -- California -- Monterey Bay -- Mathematical models; Sea breeze -- California -- Monterey Bay; Atmospheric circulation -- California -- Monterey Bay -- Mathematical models